Driving toward disability rhetorics: narrative, crip theory, and eco-ability in Mad Max: Fury Road. Issue 4 (8th August 2017) - Fletcher, Brandon; Primack, Alvin J.
ABSTRACT: We argue that the film Mad Max: Fury Road challenges stigmas associated with disability by conceptualizing a world that embraces the differences between disabled and abled bodies. Drawing on crip theory and eco-ability scholarship, we examine how Mad Max: Fury Road 's narrative criticizes normative and ableist understandings about the body by imagining a world that constructs accessible and valued spaces for the disabled. Dolmage [Dolmage, J. (2013). Disability Rhetoric . New York: Syracuse University Press] argues that scholars need to situate rhetoric on the experiences of disabled bodies to generate new meanings about disability. Mad Max: Fury Road generates such meanings by challenging normative and stigmatizing conceptions of disability through positive and nuanced representations of disabled bodies.